2012
DOI: 10.1093/brain/aws101
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying the impairment of hippocampal long-term potentiation and memory in experimental Parkinson’s disease

Abstract: Although patients with Parkinson's disease show impairments in cognitive performance even at the early stage of the disease, the synaptic mechanisms underlying cognitive impairment in this pathology are unknown. Hippocampal long-term potentiation represents the major experimental model for the synaptic changes underlying learning and memory and is controlled by endogenous dopamine. We found that hippocampal long-term potentiation is altered in both a neurotoxic and transgenic model of Parkinson's disease and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
105
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(110 citation statements)
references
References 61 publications
5
105
0
Order By: Relevance
“…PD patients frequently experience difficulty recalling past information or events 75 . The salience 18 network and the parahippocampal gyrus are consistently engaged during memory retrieval, and thus our findings are consistent with the functional role of these regions. Additionally, the salience network being affected may impair switching between networks (CEN and DMN), resulting in patients being "stuck" ie.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…PD patients frequently experience difficulty recalling past information or events 75 . The salience 18 network and the parahippocampal gyrus are consistently engaged during memory retrieval, and thus our findings are consistent with the functional role of these regions. Additionally, the salience network being affected may impair switching between networks (CEN and DMN), resulting in patients being "stuck" ie.…”
supporting
confidence: 88%
“…Thus, due to their roles in executive processing, dopaminergic dysfunction in the salience network, central executive network or the striatum which is highly interconnected with these cortical regions 16,17 could have a profound impact on memory. Alternatively, there is evidence that points to memory deficits in PD as the result of dopamine dysfunction in the medial temporal lobe 18,19 , suggesting that memory impairment may be the result of abnormal encoding or storage of memory. The aim of this study was to assess whether dopaminergic differences in executive networks 1) the central executive network, salience network or striatum or 2) the medial temporal lobe contribute to memory deficits in PD patients with mild cognitive 4 impairment.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that LTP in the CA1 area of the hippocampus is altered in both 6-OHDAlesioned rats and transgenic models of PD (mice expressing a truncated form of human a-synuclein 1 -120). This plastic alteration is associated with an impaired dopaminergic transmission and a decrease of GluN2A/N2B subunit ratio in synaptic NMDA receptors [21]. In the 6-OHDA-lesioned animals as well as in these mutant animals, the alterations of the CA1 LTP were paralleled by deficits in hippocampaldependent learning.…”
Section: Hippocampusmentioning
confidence: 95%
“…For example, 6-hydroxydopamine (6-OHDA) destroys dopaminergic neurons through free radical-mediated mechanisms (Hauser and Hastings 2013). More recently, an increasing amount of evidence has suggested that the mesohippocampal pathway is also critically involved in learning and memory processes, as indicated by the fact that many cognitive impairments, including memory deficits, occur during the early stage of PD even before the development of its classical symptoms (Whittington et al 2006;Costa et al 2012). …”
Section: Introductionmentioning
confidence: 99%